2017
DOI: 10.1186/s12902-017-0165-7
|View full text |Cite
|
Sign up to set email alerts
|

Berberine improves glucogenesis and lipid metabolism in nonalcoholic fatty liver disease

Abstract: BackgroundNonalcoholic fatty liver disease (NAFLD) is considered a critical hepatic manifestation of metabolic syndrome. Berberine (BBR) exerts anti-hyperglycemic and anti-dyslipidemic effects and can also ameliorate NAFLD. Thus, BBR might exert its therapeutic effect on NAFLD by improving glucolipid metabolism. Here, we investigated the aspects and extent to which glucolipid metabolism were affected by BBR in rats with NAFLD.MethodsThree groups of Sprague–Dawley rats were studied: a control group (n = 6) fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 26 publications
4
60
0
Order By: Relevance
“…Several studies have explored the therapeutic effects of BBR on NASH in murine models (Qiang et al, 2016;He Q. et al, 2017;Zhao et al, 2017;Feng et al, 2018;Luo et al, 2019) and humans (Chang et al, 2016;Wei et al, 2016); Qiang et al demonstrated that demethyleneberberine attenuated lipid accumulation and inflammatory factors secretion with activation of AMPK and inhibition of oxidative stress in MCD diet feeding mice and db/db mice (Qiang et al, 2016). Feng et al compared the effects of BBR, curcumin, and lovastatin on NAFLD rats and found that BBR in combination with curcumin exhibited better ameliorative effects on rats with non-alcohol fatty liver than lovastatin (Feng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the therapeutic effects of BBR on NASH in murine models (Qiang et al, 2016;He Q. et al, 2017;Zhao et al, 2017;Feng et al, 2018;Luo et al, 2019) and humans (Chang et al, 2016;Wei et al, 2016); Qiang et al demonstrated that demethyleneberberine attenuated lipid accumulation and inflammatory factors secretion with activation of AMPK and inhibition of oxidative stress in MCD diet feeding mice and db/db mice (Qiang et al, 2016). Feng et al compared the effects of BBR, curcumin, and lovastatin on NAFLD rats and found that BBR in combination with curcumin exhibited better ameliorative effects on rats with non-alcohol fatty liver than lovastatin (Feng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Ten male Wistar rats and thirty male GK rats (3 weeks old) were bred and housed locally under a 12/12-h light/darkness cycle in a temperature-controlled room (22 ± 2°C) with free access to food and water. After 1 week of acclimation, the animals were all given a high-fat diet (HFD: 40% carbohydrate, 20% protein and 40% fat) (Zhao et al 2017) for 8 weeks. Then, the animals were randomly divided into four groups and given the high-fat diet continuously for 12 weeks.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Fasting insulin (FINS) levels were also assayed at the 0th, 4th and 12th weeks using an ELISA kit (Shibayaji, Japan). Then, the homeostatic model assessment index (HOMA-IR) and the insulin sensitivity index (ISI) were calculated from the fasting blood glucose (FBG) and FINS levels using the following formulas: HOMA-IR = FBG × FINS/22.5 and ISI = ln(1/(FBG × FINS)) (Zhao et al 2017). After 12 weeks of treatment, leptin and adiponectin levels were also assayed with ELISA kits (Crystal, USA).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, BER is under investigation to determine whether it may have applications as a drug in treating diabetes, hyperlipidemia, and cancer. Recently, BER has been proven to improve glucogenesis and lipid metabolism in NAFLD (Zhao et al, 2017), perhaps mainly acting on the visceral organs in addition to the gut microbiota per se.…”
Section: Discussionmentioning
confidence: 99%